High genetic diversity and zoonotic potential of Staphylococcus aureus strains recovered from bovine intramammary infections in Colombians dairy herds. (February 2023) - Torres, G.; Vargas, K.; Reyes-Vélez, J.; Jiménez, N.; Blanchard, A.; Olivera-Angel, M.
Abstract: Genotyping of Staphylococcus aureus isolated from mastitis has become a fundamental tool to understand its complex epidemiology and to evaluate spillover events. The aim of this study was to describe the frequency of genotypes of the S. aureus strains isolated from intramammary infections by spa typing technique, and to evaluate the association between genotypes and the ability to form biofilm under in vitro conditions. Sixty-six strains of S. aureus recovered from bovines intramammary infections on 56 dairy herds located in 14 municipalities of the department of Antioquia were characterized. The majority of strains (65/66) were isolated from milk samples collected from dairy cows with subclinical intramammary infections. Nineteen different spa types were found in this study, t521 (19.70%), t267 (15.15%), and t605 (12.12%) being the most frequent. The strains from the t605 spa type showed the highest biofilm production. The high frequency of spa types with zoonotic potential found in this study, identified cattle as an important reservoir of theses clones for people in close proximity, such as milkers and consumers of unpasteurized dairy products. Highlights: High frequency of spa types with zoonotic potential were found. Differences among the ability to form biofilm and genotypes were observed. No differences among antimicrobial resistance and genotypes were identified. Molecular surveillance of S. aureus is essential to estimate the risk of spreading to community and spillover events.